2022
DOI: 10.1039/d2ya00011c
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of biowaste-derived catalysts for biodiesel production: process optimization using response surface methodology and particle swarm optimization method

Abstract: In this experimental and optimization study, banana (Musa acuminata) flower petals ash has been considered as an effective catalyst in the room temperature (28 °C) assisted transesterification to produce biodiesel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Low potassium revealed a lower catalytic activity at ORCs of 10 wt.% of the catalyst, 9 : 1 MTOR, and a 65 °C reaction temperature that yielded 92.84% of biodiesel in 285 min with a turnover frequency (TOF) of 6.59 h −1 . Laskar et al [184] also studied the preparation of a heterogeneous catalyst from Musa acuminata flower petals for biodiesel production from waste cooking oil. The catalyst preparation was done by open-air burning of the dried petal.…”
Section: Catalytic Performance Of Agricultural Waste-basedmentioning
confidence: 99%
“…Low potassium revealed a lower catalytic activity at ORCs of 10 wt.% of the catalyst, 9 : 1 MTOR, and a 65 °C reaction temperature that yielded 92.84% of biodiesel in 285 min with a turnover frequency (TOF) of 6.59 h −1 . Laskar et al [184] also studied the preparation of a heterogeneous catalyst from Musa acuminata flower petals for biodiesel production from waste cooking oil. The catalyst preparation was done by open-air burning of the dried petal.…”
Section: Catalytic Performance Of Agricultural Waste-basedmentioning
confidence: 99%
“…Biowaste-derived catalysts have been highlighted in previous papers as a potential source for catalysts to be employed in the transesterification process. Banana peel, banana trunk, and banana peduncle catalysts have already been investigated in the creation of biodiesel [43]. Odude et al [41] reported the synthesis of HSC from fruit peels, mature bananas, unripe plantains, rubber seed wastes, sugarcane bagasse, banana trunks, cocoa pod husks, flamboyant pods, and biochar-based materials.…”
Section: Utilization Of Plantain and Banana Biomass As Catalysts In B...mentioning
confidence: 99%
“…A larger surface area of the catalyst boosts its activity, and the pore structure controls how widely the active site is dispersed; therefore, it is preferable for the pore structure to be well-organized [16]. In one study, it was discovered that the capacity of the reactants to diffuse through the pores of the catalyst, which increases the synthesis of biodiesel, improved the rate of reaction when the catalyst's pore structure was linked by meso-and macroporous channels [17].…”
Section: Introductionmentioning
confidence: 99%